RANCANG BANGUN SISTEM ABSENSI LABORATORIUM UNTUK MENINGKATKAN KEEFEKTIVITASAN PENGGUNA LABORATORIUM PADA UNIVERSITAS UBUDIYAH INDONESIA - Sulvianti, Nuri (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2014)
The of science and information technology is very important in life. Absence laboratory at a university ubudiyah Indonesian (UUI) this is one way to use the space laboratory practice space that is used by student UUI. The problem is that during this time absences, sometimes easily lost damaged. In scientific writing system making laboratotium absences at the UUI district-based web. This system has several models such as the design of the grooves entity relationship diagram (ERD), data flow diagram (DFD) and programming in phplissing MySQL database. The system that will be formed that is based komputerized, which can help the process of attendance data stronge laboratorium UUI in komputerized thus formed process more effective and efficient.Keyword :Information Technology, Absence Laboratotium UUI, Web-Based.